Sistem Otomatisasi Lampu Rumah Dengan Algoritme Naive Bayes Berdasarkan Kebiasaan Penghuni Rumah - Ahmad Yazid Bastomi; Dahnial Syauqy; Issa Arwani (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
In the house function development there is term called Smart Home where the automatic system is applied to ensure the resident activities can be arrange in certain ways. One of the electronics device is automatic lamp that decrease human error and increased the efficiency use of the lamp to resident in that house. With that purpose, needed research where an automatic lamp system taking the habit data of the resident while using lamp to turn it on or off and apply that to the lamp for next day. There are three main input of the system that controlled using switch that consist of training switch that control the system mode, lamp 1 switch as input habit for lamp 1 and lamp 2 switch as input habit for lamp 2. The user habit data will recorded into Arduino UNO EEPROM in minutes then processed using Naive Bayes Algorithm to determine the output of relay module that control the lamp condition. The result of system for EEPROM accuracy data from 5 times test is 100% for switch 1 and 100% for switch 2 while main system accuracy for 12 test data is 91,6% for switch 1 and 83,3% for switch 2.